Non-Linear Narrative Structure and Time Loops as Reflective Representation of Time in The Film Sore: Istri Dari Masa Depan - Tarmawan, Irwan; Putri, Vanya Adzkia (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Films have a narrative structure designed to present the events that will be told. The film Sore: Istri dari Masa Depan adopts a non-linear narrative structure and time loop in developing its narrative, which is analyzed through a narratological approach. This research focuses on recurring time patterns in the three-act structure and their role in depicting life choices and character development. The aim of this research is to explain the structure of meaning generated through narrative, visual approaches, and temporal relationships in audiovisual texts. This research emphasizes narrative structure and depiction of time. The techniques applied include qualitative text analysis using the fabula-syuzhet framework. Bordwell, Genette’s categories of narrative time (sequence, duration, frequency), and Deleuze’s concept of the image of time. The results of this study indicate that temporal repetition functions not only as a dramatic element but also as a reflection that contributes to the gradual development of characters. Temporal patterns function structurally and visually to highlight the dimensions of relationships between individuals. These findings reveal flexibility in the narrative structure of modern Indonesian films, particularly in the romantic drama genre.